The Role of Marketing Research in Understanding Consumer Behavior and Preferences - Haris, Abdul (Advances in Business & Industrial Marketing Research, 2024)
The research aims to explore the transformative impact of digital channels and online platforms on contemporary consumer behavior, with a focus on understanding the role of social media and personalized marketing strategies. Employing a comprehensive research design, the study integrates insights from diverse disciplines, including consumer psychology, digital analytics, and economic considerations. Methodologically, a systematic literature review and qualitative analysis are conducted to synthesize findings from recent research studies, providing a nuanced understanding of the dynamics shaping consumer-brand interactions in the digital age. The findings highlight the significance of digital channels in reshaping consumer preferences and purchasing decisions, emphasizing the role of social media platforms and personalized experiences in driving brand engagement and loyalty. Implications for businesses include the necessity to adopt digital-first approaches, leverage advanced analytics tools, and prioritize consumer-centric strategies to remain competitive in the evolving marketplace. Additionally, the study underscores the importance of interdisciplinary perspectives and ongoing research efforts to explore emerging trends and technologies that continue to shape consumer behavior and market dynamics.